The Role of Parents in the Referral Process to Inclusive Education in Macao - Tam, Ka In (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.

Father’s Involvement and Parenting Styles in Macao - Chan, Ieng Chong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Home–School Collaboration in Assessment, Placement, and Individual Education Plan Development for Children With Special Education Needs in Macao: The Views of Parents - Correia, Ana; Teixeira, Vitor; Forlin, Chris (School Community Journal, 2021)
The aim of this study was to explore home–school collaboration in the areas of assessment, placement, and Individual Education Plan (IEP) development for children identified with disabilities or special educational needs (SEN) in Macao. Despite the noted benefits of parent–school partnerships from prior research, minimal research has been conducted from the perspective of parents of children with SEN to examine whether these partnerships materialize in the context of Macao. Participants included 115 parents of school-aged children diagnosed with SEN. They provided demographic information and completed a 36-item questionnaire derived from two validated instruments. The research identified a range of factors which hinder parental involvement in decision-making and in the inclusion of children with SEN in optimal ways in Macao schools. Parents indicated they were not receiving relevant information and assessment feedback from the teachers; they were minimally involved in the IEP process, and their children were not receiving one-to-one support, regardless of the type of placement. Parents also underlined issues related to the timing of assessment procedures. Parents of children attending special classes in regular schools voiced more satisfaction with support provision than parents of children following the full inclusion model. Recommendations about how services could be improved for greater parental involvement are discussed. Key Words: parental involvement, school–family collaboration, inclusion, special educational needs, Macao, Individual Education Plans, IEP

Parental Involvement and Child Development in Macao: Association with Family Income, Parental Education and Working in the Gambling Industry - Kung, Hang I (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Association Between Early/ Emerging Adult-Parent Attachment and Problematic Internet Use Among College Students in Macao - Lao, Sio Mei (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

O Autoconceito no Pré-Escolar em Contexto Educativo Multicultural e Plurilinguίstico=Preschool Children’s Self-concept in a Multicultural and Multilingual Educational Context - Sousa, Joana Luísa Dourado de (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Experiences and Reflections Related to Mental Health Among University Students during Covid-19: A Case Study - Tou, Un Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Role of Cognition as a Mediator for Narcissism and Trait Aggression as Predictors of Aggressive Driving Behavior - Van, Hou Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The use Robotics in the intervention with children with ASD in Macao: a pilot study with Milo - Teixeira, Vitor; Lai, Michael (Revista Portuguesa de Investigação Educacional, 2021)
Robotics are being used in the intervention with children with Autism Spectrum Disorder (ASD) in many places and already for many years. Many robots were developed and different studies are being made in order to evaluate its effectiveness. “Socially Assistive Robotics” is shown to be effective in different areas mainly in social and emotional development. Milo, a robot developed by a team led by Richard Margolin for the Robots4Autism program (RoboKind, 2020), is one of the robots whose use is reported to be successful. In Macao there is no report of studies or experiences on the use of robots in the intervention with children with ASD. In a collaboration between the Macao Science Centre, the Macao Autism Association (MAA) and the University of Saint Joseph, an exploratory study was developed to understand the applicability of Milo to the work with children with ASD in Macao. The study showed that the robot is able to facilitate social and emotional competences of children with ASD. However, several limitations including language, cultural differences, the inexperienced facilitators and the level of sessions are too simple for the participants to be aware of that may affect the effectiveness of the intervention. It is important to show that the adoption of Milo in Macao for intervening children with ASD can be further implemented, with better practical solutions.

Clothing and School Uniforms in Macau: Maria João Nunes Das - Das, Maria João Nunes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Art-Based Intervention For Children with ADHD: Catina Fong Chi Cheng - Fong Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Association Between Interpersonal Relationships and Mental Health in College Students in Macao - Guo, Peiling (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Problematic Internet Use and Subjective Wellbeing Among University Students in Macao - Kam, Chi Fat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

CASE STUDY ON ART INTERVENTION WITH CHILDREN WITH AUTISM SPECTRUM DISORDER - Wu, Hoi Pio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph